Lika Liku Kesuksesan Air Traffic Flow Management di Bandara Internasional I Gusti Ngurah Rai - Bara Jiwangganata M.; I Gede Sanica (Jurnal Manajemen dan Bisnis, 2021)
This research aims to determine and examine mountainously about the satisfaction of airlines and Perum lppnpi management through of air traffic flow management in I Gusti Ngurah Rai International Airport. This research used qualitative method with research subject namely airline, ATFM Operator and Perum lppnpi management. Data collection technique was carried out by in-depth interview. Researchers implement the adoption Zeithaml and Bitner's Servqual Technique. The result of data analysis in this study indicate that the quality of service through ATFM are well guarded, but significantly factor of that quality is reliability, why? Because the consumer has been satisfied with a good service, fast and punctuality.